Perdebatan isu Productivity Linked Wages System(PLWS) dalam Perundingan Kolektif Kesatuan Sekerja Perbankan Sabah - Kee.Y.Sabariah Kee Mohd Yussof; Mahadirin Hj Ahmad (Sosio Humanika, 2009)
This paper discusses about Sabah Banking Employee Union members perception on their collective bargaining (2003-2005) on salary and payment. In their particular collective bargaining, SBEU members struggle to obtain 10 to 12 percent increament in their salary and payment. In this case, employer give them only 5% increament based on Consumer Price Indeks were lower (1.4%) during the negotition. It’s took 21 month to negotiate and finally they come to dead lock situation. Then, SBEU invites the third party from Industrial Relation Department as a mediator in their collective bargaining process. During the last stage of negotition, the employers offered more than 5% increament in salary payment but the annual bonus would be eliminated. In this case, employers would consider the performance bonus which is evaluated from workers performance annualy. SBEU could not accept the offer as the employees would lose their annual bonus and it’s difficult to regain it back later. In positive way, the employers try to introduce the Productivity Linked Wages System in their organisation but members of SBEU disagreed with the suggestion based on saveral factors